2015
DOI: 10.1016/j.jtcvs.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antegrade versus integrated blood cardioplegia on left ventricular function evaluated by echocardiographic real-time 3-dimensional speckle tracking

Abstract: These findings by 3-dimensional transthoracic speckle tracking echocardiography indicate that integrated cardioplegia offers superior myocardial protection of the left ventricular free wall and septum compared with the antegrade mode of cardioplegia delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is well known that septum dysfunction is commonplace after cardiac surgery, as 43% of 3292 patients [ 105 ] develop septal paradoxical motion (lesser damage was not reported). Impaired myocardial protection causes this injury, but this damage can be avoided [ 128 ], as undamaged hearts show improved longitudinal helical deformation [ 129 ].…”
Section: Diastolic Dysfunctionmentioning
confidence: 99%
“…It is well known that septum dysfunction is commonplace after cardiac surgery, as 43% of 3292 patients [ 105 ] develop septal paradoxical motion (lesser damage was not reported). Impaired myocardial protection causes this injury, but this damage can be avoided [ 128 ], as undamaged hearts show improved longitudinal helical deformation [ 129 ].…”
Section: Diastolic Dysfunctionmentioning
confidence: 99%
“…Three‐dimensional speckle‐tracking imaging (3DSTI) can track the motion of the speckles in a real time and angle‐independent manner and thus can evaluate left ventricular (LV) function more comprehensively and accurately . However, the role of 3DSTI, two‐dimensional echocardiography (2DE), and magnetic resonance imaging (MRI) in detecting left ventricular ejection fraction (LVEF) in patients with primary dilated cardiomyopathy (DCM) remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that septal dysfunction after cardiac surgery is related to inadequate myocardial protection and that it can be prevented by specific cardioplegic techniques. 16 We have also shown that antegrade cardioplegia alone caused reduction in longitudinal strain, a variable that was normal after integrated antegrade and retrograde cardioplegia. The uninjured septum prevents RV dysfunction.…”
mentioning
confidence: 62%